We first obtain the equation of the lines bounding R.
For the line with points (0, 0) and (8, 1), the equation is given by:
![\frac{y}{x} = \frac{1}{8} \\ \\ \Rightarrow x=8y \\ \\ \Rightarrow8u+v=8(u+8v)=8u+64v \\ \\ \Rightarrow v=0](https://tex.z-dn.net/?f=%20%5Cfrac%7By%7D%7Bx%7D%20%3D%20%5Cfrac%7B1%7D%7B8%7D%20%20%5C%5C%20%20%5C%5C%20%5CRightarrow%20x%3D8y%20%5C%5C%20%20%5C%5C%20%5CRightarrow8u%2Bv%3D8%28u%2B8v%29%3D8u%2B64v%20%5C%5C%20%20%5C%5C%20%5CRightarrow%20v%3D0)
For the line with points (0, 0) and (1, 8), the equation is given by:
![\frac{y}{x} = \frac{8}{1} \\ \\ \Rightarrow y=8x \\ \\ \Rightarrow u+8v=8(8u+v)=64u+8v \\ \\ \Rightarrow u=0](https://tex.z-dn.net/?f=%20%5Cfrac%7By%7D%7Bx%7D%20%3D%20%5Cfrac%7B8%7D%7B1%7D%20%20%5C%5C%20%20%5C%5C%20%5CRightarrow%20y%3D8x%20%5C%5C%20%20%5C%5C%20%5CRightarrow%20u%2B8v%3D8%288u%2Bv%29%3D64u%2B8v%20%5C%5C%20%20%5C%5C%20%5CRightarrow%20u%3D0)
For the line with points (8, 1) and (1, 8), the equation is given by:
![\frac{y-1}{x-8} = \frac{8-1}{1-8} = \frac{7}{-7} =-1 \\ \\ \Rightarrow y-1=-x+8 \\ \\ \Rightarrow y=-x+9 \\ \\ \Rightarrow u+8v=-8u-v+9 \\ \\ \Rightarrow u=1-v](https://tex.z-dn.net/?f=%20%5Cfrac%7By-1%7D%7Bx-8%7D%20%3D%20%5Cfrac%7B8-1%7D%7B1-8%7D%20%3D%20%5Cfrac%7B7%7D%7B-7%7D%20%3D-1%20%5C%5C%20%20%5C%5C%20%5CRightarrow%20y-1%3D-x%2B8%20%5C%5C%20%20%5C%5C%20%5CRightarrow%20y%3D-x%2B9%20%5C%5C%20%20%5C%5C%20%5CRightarrow%20u%2B8v%3D-8u-v%2B9%20%5C%5C%20%20%5C%5C%20%5CRightarrow%20u%3D1-v)
The Jacobian determinant is given by
![\left|\begin{array}{cc} \frac{\partial x}{\partial u} &\frac{\partial x}{\partial v}\\\frac{\partial y}{\partial u}&\frac{\partial y}{\partial v}\end{array}\right| = \left|\begin{array}{cc} 8 &1\\1&8\end{array}\right| \\ \\ =64-1=63](https://tex.z-dn.net/?f=%20%20%5Cleft%7C%5Cbegin%7Barray%7D%7Bcc%7D%20%5Cfrac%7B%5Cpartial%20x%7D%7B%5Cpartial%20u%7D%20%26%5Cfrac%7B%5Cpartial%20x%7D%7B%5Cpartial%20v%7D%5C%5C%5Cfrac%7B%5Cpartial%20y%7D%7B%5Cpartial%20u%7D%26%5Cfrac%7B%5Cpartial%20y%7D%7B%5Cpartial%20v%7D%5Cend%7Barray%7D%5Cright%7C%20%3D%20%5Cleft%7C%5Cbegin%7Barray%7D%7Bcc%7D%208%20%261%5C%5C1%268%5Cend%7Barray%7D%5Cright%7C%20%5C%5C%20%20%5C%5C%20%3D64-1%3D63)
The integrand x - 3y is transformed as 8u + v - 3(u + 8v) = 8u + v - 3u - 24v = 5u - 23v
Therefore, the integration is given by: